Faktor – Faktor yang Mempengaruhi Saluran Distribusi PT Tirta Investama Surabaya - Muhammad Hijri Ismail; Lia Nirawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Several things that must be considered so that marketing activities run well and smoothly, one of which is distribution channels. Distribution channels include all activities related to the business of conveying goods produced by a producer company to buyers or potential consumers. The purpose of this research is to determine the factors that influence distribution channels. The type of research used by researchers is quantitative research. In this research, the Non Probability Sampling method was used with the technique used, namely Purpose Sampling, so that 2 types of vehicles were obtained, namely the L 300 pick-up and the crank truck. 12 units of L 300 pick up and 4 units of auto trucks. The data collection technique in this research uses secondary data. Data analysis techniques use multiple linear regression analysis, validity testing, normality testing, and hypothesis testing. The research results show that market coverage and goods can simultaneously influence distribution channels, partial market coverage can influence distribution channels, goods can partially influence distribution channels